Denaturation of Proteins by SDS and by Tetra-alkylammonium Dodecyl Sulfates - Lee, Andrew (2011)
This paper describes the use of capillary electrophoresis (CE) to examine the influence of different cations (C(+); C(+) = Na(+) and tetra-n-alkylammonium, NR(4) (+), where R = Me, Et, Pr, Bu) on the rates of denaturation of bovine carbonic anhydrase II (BCA) in the presence of the anionic surfactant dodecylsulfate (DS(−)). Analysis of the denaturation of BCA in solutions of Na(+)DS(−) and NR(4) (+)DS(−) (in Tris-Gly buffer) indicated that the rates of formation of complexes of denatured BCA with DS(−) (BCA(D)-DS(−)(n,sat)) are indistinguishable and independent of the cation below the critical micellar concentration (cmc), and independent of the total concentration of DS(−) above the cmc. At concentrations of C(+)DS(−) above the cmc, BCA denatured with rates that depended on the cation; the rates decreased by a factor > 10(4), in the order Na(+) ~ NMe(4) (+) > NEt(4) (+) > NPr(4) (+) > NBu(4) (+) – the same order as the values of cmc (which decrease from 4.0 mM for Na(+)DS(−) to 0.9 mM for NBu(4) (+)DS(−) in Tris-Gly buffer). The relationship between values of cmc and rates of formation of BCA(D)-DS(−)(n,sat) suggested that the kinetics of denaturation of BCA involve the association of this protein with monomeric DS(−), rather than with micelles of (C(+)DS(−))(n). A less-detailed survey of seven other proteins (α-lactalbumin, β-lactoglobulin A, β-lactoglobulin B, carboxypeptidase B, creatine phosphokinase, myoglobin, and ubiquitin) showed that the difference between Na(+)DS(−) and NR(4) (+)DS(−) observed with BCA was not general. Instead, the influence of NR(4) (+) on the association of DS(−) with these proteins depended on the protein. The selection of cation contributed to the properties (including composition, electrophoretic mobility, and partitioning behavior in aqueous two-phase systems) of aggregates of denatured protein and DS(−). These results suggest that variation in the behavior of NR(4) (+)DS(−) with changes in R may be exploited in methods for analyzing and separating mixtures of proteins.